PENERAPAN APLIKASI POINT OF SALES PADA UMKM MAKANAN JADOEL DI TEMBILAHAN - Bal, Iqbal (ABDIMAS : Jurnal Pengabdian Masyarakat, 2023)
Jadoel Food is a micro, small and medium enterprise (MSME) which operates in traditional Tembilahan food. Before using the POS application, Jadoel Food UMKM managed stock manually. This process can be complicated, time consuming and increases the risk of errors in stock recording. By implementing the POS application, Jadoel Food MSMEs are expected to be able to overcome these challenges and gain a number of benefits, including increased operational efficiency, stock accuracy, transaction speed and better data analysis. Implementing a POS application can be a strategic step to increase competitiveness and business growth in the food sector. Without a POS application, MSME owners may have difficulty getting real-time financial information. Sales and financial reports may take a long time to prepare.